2007
DOI: 10.1002/ajp.20383
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid levels in free ranging resident mantled howlers: a study of coping strategies

Abstract: A growing amount of data shows that a preference for passive-nonaggressive over active-aggressive problem solving is associated with higher levels of glucocorticoids (GC). For mantled howlers, the arrival of an adult male in a new group is a potential source of psychological stress for both resident males and females. Resident mantled howler males take an active stand and aggressively repel the entrance of solitary males, while females take a passive-nonaggressive stand. In order to study whether the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Nonetheless, mean male fecal androgen levels per group were positively correlated with the number of extragroup males living in the same forest fragment, suggesting that mantled howler males on average exhibited a hormonal response proportional to the potential threat posed by solitary males (Cristóbal-Azkarate et al 2006 ). Fecal glucocorticoid levels averaged across all sampled males per group were not signifi cantly correlated, while those averaged across all sampled females per group were positively correlated with the number of solitary males living in the same forest fragment (Cristóbal-Azkarate et al 2007 ). The authors suggested that differences in the ways in which males and females cope with stressful, unpredictable situations posed by the presence of extragroup males in their forest fragment may account for different mean fecal glucocorticoid levels among resident males and females.…”
Section: Socioendocrinologymentioning
confidence: 81%
See 2 more Smart Citations
“…Nonetheless, mean male fecal androgen levels per group were positively correlated with the number of extragroup males living in the same forest fragment, suggesting that mantled howler males on average exhibited a hormonal response proportional to the potential threat posed by solitary males (Cristóbal-Azkarate et al 2006 ). Fecal glucocorticoid levels averaged across all sampled males per group were not signifi cantly correlated, while those averaged across all sampled females per group were positively correlated with the number of solitary males living in the same forest fragment (Cristóbal-Azkarate et al 2007 ). The authors suggested that differences in the ways in which males and females cope with stressful, unpredictable situations posed by the presence of extragroup males in their forest fragment may account for different mean fecal glucocorticoid levels among resident males and females.…”
Section: Socioendocrinologymentioning
confidence: 81%
“…Finally, comparison of glucocorticoid levels between males and females has revealed that females of mantled howler monkeys appear to be more sensitive than males to either social (e.g., threat of extragroup males in habitat; Cristóbal-Azkarate et al 2007 ) or ecological stressors (e.g., translocation and human handling; AguilarCucurachi et al 2010 ), information that could only have been identifi ed by combining behavioral observations with endocrine studies.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Some research methods used for hormone extraction are based on the selection of a solvent, the application of temperature (Gao and Liu, 2005), the types and time of agitation, using moist feces (Heistermann et al, 1996; Wasser et al, 2000; Hunt and Wasser, 2003; Hunt et al, 2004; Cristóbal-Azkarate et al, 2007) nor lyophilized feces (Wasser et al, 1997, 2004; Goymann et al, 1999; Khan et al, 2002; Hunt et al, 2004) from diverse species of mammals. Also in these studies include the evaluation of free ligand activity added to the substratum and validation of the assay (Buchanan and Goldsmith, 2004; Palme et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Using these techniques, the effect of stressful situations like forest fragmentation in the habitat of Alouatta pigra monkeys [8] , or how a group of Alouatta palliata species solve stressful problems created for example by the arrival of a new male to a resident group [9] have been published. Influences on fecal cortisol of environmental conditions such as forest conservation have been recently reported in free-living Yucatan spider monkeys [10] .…”
Section: Primates: Glucocorticoids and Steroid Reproductive Hormones mentioning
confidence: 99%